Total Quality Management for Islamic financial institutions - Islam, Rafikul (International Council of Islamic Financial Educators, 2016)
The book deals with the issues how TQM principles can be applied to improve quality for Islamic financial institutions. There are 8 chapters, 1. Introduction to TQM, 2. Customer Satisfaction, 3. Engaging Employees through Suggestion System, 4. Continuous Improvement, 5. Benchmarking, 6. National Quality Awards, 7. Quality Function Deployment, 8. Six Sigma Program. In addition to discussing the TQM principles, the author has shown how these principles can be applied to Islamic financial institutions by means of examples. The book is expected to be useful guide to the Islamic banking practitioners.